Moving megaliths in the Neolithic - a multi analytical case study of dolmens in Freixo-Redondo (Alentejo, Portugal) - Boaventura, Rui (2020)
In this work a multi-disciplinary and multi-analytical approach was developed with the aim of better understanding the effort and selection criteria involved in the search for slabs used for the construction of dolmens during the Neolithic. Nine dolmens within a strip with ~15x10 km2 on south Portugal (Freixo, Alentejo region), within magmatic and metamorphic geological basement were studied. Based on their chronology and geographic positioning the dolmens studied were systematized as follows: dolmens of the Freixo Group (7), dolmen of Godinhos (1) and dolmen of Candeeira (1). The work developed consisted of an intensive geological survey associated with a sampling protocol. These data combined with the results obtained through microscopy and whole-rock geochemistry on samples from dolmens and outcrops allow us to infer some conclusions about distances involved. The nearest exposures were not used as the unique collection site. Although the distances from dolmen to nearest outcrops varies between 150 m and 780 m the complete match including size, shape, petrography and geochemistry was obtained for several dolmens providing for group of Freixo, distances between 800 and 3500 m, the dolmen of Godinhos use very local material ~350 m, and for dolmen of Candeeira, a local provenance of 170 m was established based on singular macroscopic features. Other nearby, available lithology (gabbro) and with compatible size was deprecated due to other reasons than functional.